Organizational journeys toward strong cultures of sustainability: a qualitative inquiry - Riemer, Manuel; Marcus, Joel; Reimer-Watts, Benjamin Kai (Frontiers in Psychology, 2025)
IntroductionThere is widespread belief that organizational culture plays a crucial role in transitioning organizations for sustainability, but we currently lack understanding of how supportive cultures develop. The goal of this study is to empirically investigate how a culture of sustainability (COS) develops within a varied sample of real-world organizations.MethodsA qualitative cross-sectional design was utilized in this study using 14 semi-structured qualitative interviews with leaders of organizations perceived as having a strong COS or being on a good path toward that. The interviews explored how the leaders from various organizations experienced the development process of a COS from the initial emergence to the time of the interview. The qualitative data were analyzed using template analysis combined with applying a team-based approach to open coding.ResultsThe results indicate that while COS development is not a direct, clear, or linear process, there are several common factors that descriptively capture the process of COS formation. The analysis revealed four general stages of COS development (emergence; visibility and engagement; institutionalization and system alignment; ingrained and habitualized practice) and three key contextual moderators (organizational characteristics; external stakeholders/societal culture; business case).DiscussionThis study makes an important contribution to the limited empirical literature on the development of organizational culture over time. Understanding key factors, relationships between factors, and COS stages can help leaders establish realistic expectations and strategies for developing and strengthening COS within their organizations.